Verification of the Effects of Red Light-emitting Diode Therapy on Acute Lung Injury in a Sepsis Model in Rats - Alves,Willer Eduardo (2020)
Abstract The aim of this study was to evaluate the in vivo response of red light-emitting diode (LED) on acute lung injury (ALI) in a sepsis model in rats. Twenty rats were randomly allocated into two experimental groups (n=10): Control Sepsis Group (CS); sepsis and red LED group (SRL). The anterior region of the trachea and ventral regions of the chest (below the ribs), bilaterally were irradiated daily for two consecutive days, starting immediately after the surgery using red (630 nm) LED. The histological results showed that in red LED treated group presented a modulation of the lung inflammatory process, less intense alveolar septum thickening and decrease of the inflammatory cells. Moreover, LED significantly reduced the lung injury score and increased interleukin type 10 (IL-10) protein expression compared SG. These results suggest that LED was efficient in attenuating ALI in a sepsis model in rats by reducing inflammatory cells into lung tissue and enhancing the anti-inflammatory cytokine production.